Prepubertal Serum Testosterone Concentration In Vembur Rams At Different Rearing System - Selvakumar, R; Sivakumar, T; Kumar, S Ganesh; Anuradha, P (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present investigation was carried out to study the prepubertal testosterone pattern and age at puberty in Vembur rams reared under farm and farmers field condition. A total number of 8 Vembur ram lambs each from farm and farmers field were selected. The measurement of testosterone was performed by Radioimmunoassay (RIA). The serum testosterone level from 6th to 20th month of age ranged from 0.132 ± 0.04 to 3.823 ng/ml in semi intensively maintained farm males and 0.138±0.04 to 3.456±0.17 ng/ml in animals maintained at farmer’s holdings. The serum testosterone levels were crossing the concentration of 2.5 ng/ml at the age of 17 to 18th weeks and successful mounting, intromission and ejaculation were noticed after this age.